Analisis Tata Letak Gudang Produksi di PT Nusantara Sejahtera Medica - Umayatul Azizah; Denny Murdani (Fakultas Ekonomi Universitas 45 Surabaya, 2024)
Tight business competition encourages companies to manage resources optimally and create competitive advantages. Operations management, which includes managing inputs, processes, and outputs, plays an important role in achieving these goals. Warehouses are an important part of a company's supply chain, functioning as a place to store goods inventory and support the smooth production and operational processes. Optimal warehouse layout influences smooth operations, optimizes space, and supports the production process. PT Nusantara Sejahtera Medica is a company engaged in the production of organic fertilizer and health supplements in West Bandung Regency, currently using a